Serum IgE levels of healthy children in the Trabzon region of Turkey - Mocan, Hilal; Saraçlar, Yıldız (The Turkish Journal of Pediatrics, 1988)
Serum IgE levels were determined in 49 non-atopic children following the evaluation of the results obtained from questionnaires regarding allergic disorders in 431 primary school children in the Trabzon Region of Turkey. IgE levels were found to be significantly higher than the levels obtained in Samsun and in Ankara. The importance of determining serum IgE levels in various regions of a country is also discussed.
Keywords: immunoglobulin E; atopy; parasitosis